2015
DOI: 10.1021/acs.energyfuels.5b00297
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Upgrading of Anisole with Hydrogen Catalyzed by Platinum Supported on Alumina

Abstract: Kinetics of the reactions of anisole, a model compound representative of lignin-derived bio-oils, with H 2 , catalyzed by Pt/Al 2 O 3 , were investigated with a fixed-bed tubular microflow reactor at 573−673 K, 8−14 bar, and space velocities in the range of 3−240 (g of anisole)/(g of catalyst × h). Selectivity−conversion data were used as a basis to propose an approximate reaction network and estimate parameters in approximate rate equations. The reactions include the following: anisole conversion to phenol by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
3
38
1
Order By: Relevance
“…In this research, we extend the work that has been reported characterizing sulphided CoMo/γ‐Al 2 O 3 ‐catalyzed hydroprocessing of compounds representative of lignin‐derived bio‐oils, now including a partial quantitative representation of the reaction network (with kinetics), with 4‐methylanisole chosen as the reactant because it incorporates a benzene ring substituted with both methyl and methoxy groups and is therefore a good representative of lignin‐derived compounds.…”
Section: Introductionmentioning
confidence: 86%
“…In this research, we extend the work that has been reported characterizing sulphided CoMo/γ‐Al 2 O 3 ‐catalyzed hydroprocessing of compounds representative of lignin‐derived bio‐oils, now including a partial quantitative representation of the reaction network (with kinetics), with 4‐methylanisole chosen as the reactant because it incorporates a benzene ring substituted with both methyl and methoxy groups and is therefore a good representative of lignin‐derived compounds.…”
Section: Introductionmentioning
confidence: 86%
“…The depolymerization of biomass and the upgrading the resulting fragments into compounds with properties that approximate those of petroleum represent substantial challenges . The compositions of liquids formed from biomass depend on the raw materials and the methods of conversion . Generally, these liquids include high concentrations of oxygen‐containing compounds, and improvements in the stability of these liquids and their compatibility with petroleum products require a reduction in their oxygen contents.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various polymers present in lignocellulosic biomass, lignin, with its polyaromatic structure, is the one that is chemically most similar to petroleum. Nonetheless, lignin contains much more oxygen than crude oil , and lignin‐derived bio‐oils are good candidates for hydroprocessing for oxygen removal.…”
Section: Introductionmentioning
confidence: 99%
“…The utilized microflow reactor (Microactivity‐Reference, PID Eng & Tech) for the conversion of cyclohexanone has been well introduced in the previous studies . A fixed‐bed once‐through tubular reactor working in the down‐flow mode and equipped with a porous plate for the catalyst particles was utilized.…”
Section: Methodsmentioning
confidence: 99%